Sustainable drainage retrofit case study: Counters Creek Flood Alleviation Scheme, UK. Issue 4 (14th June 2021) - Casares, Pablo Souto; Benton, Laura; Bull, Jack
Abstract : While the implementation of sustainable drainage systems (SuDS) is becoming widespread in new developments, the retrofitting of SuDS is emerging as a technique on its own, with the added risks of having to adapt to established built environments and communities. The Counters Creek Flood Alleviation Scheme in the UK, a project implemented by Thames Water to reduce flood risk to over 1500 basement properties across Hammersmith and Fulham, and Kensington and Chelsea in the UK, adopted these solutions to achieve the project goals and deliver multiple benefits to the residents. Six SuDS schemes were implemented in different residential streets in the London Borough of Hammersmith and Fulham, which had been previously selected with the use of innovative tools in catchment analysis. The project delivered design and construction against its milestones with a collaborative approach between all parties involved.